Pengendali Kecepatan Motor DC Terhadap Perubahan Suhu Menggunakan PLC dan Human Machine Interface - Anisah, Masayu; Amperawan, Amperawan; Rasyad , Sabilal; Yani , Herman; Firmansyah, Anton (Universitas PGRI Palembang, 2023)
Controlling the speed of a DC motor in proportion to changes in temperature of a K-type thermocouple uses a Programmable Logic Controller and the Human Machine Interface to enable monitoring of the temperature and speed of the Direct Current motor from changes in the thermocouple sensor as input in the form of temperature data reduced to analog. to digital converter in the form of digital data and controls the speed of the DC motor by adjusting the Pulse Width Modulation. DC motor speed control for temperature changes from a thermocouple sensor with a control system using a Programmable Logic Controller and displayed on the Human Machine Interface. In this test, only heating the sensor at a temperature of 30 oC to 100 oC and the speed of the DC motor where the temperature is greater, the PWM value makes the DC motor rotate faster. In controlling DC motors with PWM using a frequency of 10 Hz to get a PWM value of 0% - <54% the motor will rotate at low speed. PWM 54% - <84%, the motor will rotate at medium speed. PWM 84% - >90%, the motor will rotate at high speed